Evaluating arctic dialogue: A case study of stakeholder relations for sustainable oil and gas development - Makki, Muhammad (Journal of Sustainable Development, 2012)
Companies have increasingly adopted stakeholder dialogue and engagement processes to address stakeholder concerns and increase trust, mutual understanding, and to provide better processes of communication regarding their activities. To foster dialogue and increase information sharing between various stakeholders for Arctic oil and gas development, a series of dialogues have been initiated by Bodø Graduate School of Business (Norway), High North Center of Business and Governance (Norway), and public relations firm HBW Resources (USA), called Arctic Dialogue. The purpose of article is to evaluate from the perspective of communication and stakeholder theory. Furthermore the article describes key features and the role of Arctic Dialogue in shaping mutual understanding. In general the findings present an overview of perceptions and impact of the Dialogue process and suggest that Arctic Dialogue is an effective and appropriate activity to integrate stakeholders, information sharing and create mutual understanding.